Erratum to “Systematic Development of Short-Term Load Forecasting Models for the Electric Power Utilities: The Case of Pakistan” - Aneeque A. Mir (IEEE, 2021)
In the above article [1], Fig. 3 (a) and (b) and Fig. 5 (a) and (b) were inadvertently duplicated during the proofreading and typesetting stage. This resulted in Fig. 3 (a) and (b) in [1] not representing the correlation of load with dry bulb temperature and dewpoint temperature as intended and stated in the figure caption. The correct representation of the correlation of load with both the dry bulb temperature and dewpoint temperature to be considered is shown below in Fig. 3. However, Fig. 5 (a) and (b) in [1] already correctly represents the average dry bulb temperature of eight weather stations and the average dew point temperature of eight weather stations. Therefore, Fig. 3 given below should replace Fig. 3 (a) and (b) in [1].